Asesoría diocesana sobre inmuebles y cuestiones edilicias:: perjuicios de su ausencia y propuesta de lege ferenda - Di Nicco, Jorge Antonio (Universitas Canónica, 2022)
The present work deals with diocesan advice on real estate and building issues, a subject on which the bibliography is not abundant, explaining its importance and the need for each diocesan curia to have it. It develops the qualities that its members must possess, their function, term of appointment and retribution, among other aspects. A statistic about its existence is presented in particular Churches of Argentina, Brazil, Chile and Uruguay; pointing out the case of a diocese that has counted on the Counseling for almost twenty years. Finally a lege ferenda proposal is made. The work is introduced in a subject that has not yet been deepened and that deserves to be.